2020
DOI: 10.1177/2309499020915106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tibiofemoral joint forces on patient-reported outcome measurements after bicruciate stabilized total knee arthroplasty

Abstract: Objective: Insall advocated that a successful clinical outcome of total knee arthroplasty (TKA) depends on soft tissue balance procedure. Spacer blocks, balancer, and instrumented tibial sensor (VERESENSE, OrthoSensor, Dania, Florida, USA) are the current methods of soft tissue balancing during TKA. The purpose of the study is to assess intraoperative medial and lateral tibiofemoral compressive force (TFCF) using novel insert sensor and investigate the relationship between TFCF and patient-reported outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…1 (Additional file 2). Median MINORS for non-comparative studies value was 11.5 (11)(12), and for comparative studies 18.2 (13)(14)(15)(16)(17)(18)(19)(20)(21). Median Jadad Scale score was 3.6 (2)(3)(4)(5).…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…1 (Additional file 2). Median MINORS for non-comparative studies value was 11.5 (11)(12), and for comparative studies 18.2 (13)(14)(15)(16)(17)(18)(19)(20)(21). Median Jadad Scale score was 3.6 (2)(3)(4)(5).…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 98%
“…Nine studies examined the rate of MUA as an assessment of postoperative arthrofibrosis (Table 2 ). Geller et al reported that the rate of MUA in the MB TKA group was higher than in the VA TKA group, and that the period between TKA and MUA was on average 13.5 weeks and 7.5 weeks, respectively [ 15 ]. Some of the other studies also showed higher rates of MUA in the MB TKA group, but with no significant differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] This is because soft tissue balance is a key factor that affects the lifetime of the knee prosthesis and the postoperative mobility of the patient's knee joint. [11][12][13][14] It is noted that soft tissue balance measurement is also a key factor affecting TKA surgery performed using knee joint replacement surgery robots. Thus, an accurate measurement of soft tissue balance plays a vital role in TKA.…”
Section: Introductionmentioning
confidence: 99%